PERIOPERATIVE DYNAMICS OF INTRAOCULAR PRESSURE DURING CONTINUOUS ESKETAMINE ANALGOSEDATION IN COMBINED CATARACT AND GLAUCOMA SURGERY: A CASE REPORT: PERIOPERATIVE CHANGES IN INTRAOCULAR PRESSURE DURING ESKETAMINE ANALGOSEDATION - Lučić, Margita; Marjanović, Ivan; Vasović, Dolika D. (Srpski medicinski časopis Lekarske komore, 2026)
Introduction: Perioperative management of patients with glaucoma requires a precise balance between maintaining systemic hemodynamic stability and preserving adequate ocular perfusion pressure. The effects of esketamine on intraocular pressure (IOP) during glaucoma surgery remain insufficiently investigated. Case report: We report the case of a 45-year-old female patient diagnosed with cataract and chronic glaucoma, without significant associated comorbidities, who underwent combined phacoemulsification with intraocular lens implantation and trabeculectomy. The surgical procedure was performed under subtenon anestesia, combined with targeted continuous esketamine analgosedation at a subanesthetic dose, administered as a continuous infusion at a rate of 0.25 mg/kg/h. During the perioperative period, hemodynamic parameters, peripheral oxygen saturation, pain intensity, level of sedation, and intraocular pressure were monitored at multiple predefined perioperative time points. The baseline intraocular pressure was 39 mmHg; following stabilization of sedation, it decreased to 26 mmHg, with a further reduction to 11 mmHg observed in the early postoperative period. No hemodynamic instability, respiratory depression, or need for additional supportive analgesia was recorded during surgery. Conclusion: This case report suggests that continuous subanesthetic esketamine analgosedation is a feasible option during combined cataract and glaucoma surgery performed under sub-Tenon’s anesthesia, providing stable hemodynamics, preserved spontaneous respiration, good patient cooperation, and a favorable early perioperative intraocular pressure profile in the presented case. Further prospective studies are required to confirm these findings.